2001
DOI: 10.1021/ic010162b
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and Formation Kinetics of Sitting-Atop (SAT) Complexes of Some Porphyrins with Copper(II) Ion in Aqueous Acetonitrile Relevant to Porphyrin Metalation Mechanism. Structures of Aquacopper(II) and Cu(II)−SAT Complexes As Determined by XAFS Spectroscopy

Abstract: The formation of the sitting-atop (SAT) complexes of 5,10,15,20-tetraphenylporphyrin (H(2)tpp), 5,10,15,20-tetrakis(4-chlorophenyl)porphyrin (H(2)t(4-Clp)p), 5,10,15,20-tetramesitylporphyrin (H(2)tmp), and 2,3,7,8,12,13,17,18-octaethylporphyrin (H(2)oep) with the Cu(II) ion was spectrophotometrically confirmed in aqueous acetonitrile (AN), and the formation rates were determined as a function of the water concentration (C(W)). The decrease in the conditional first-order rate constants with the increasing C(W) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 49 publications
5
67
2
Order By: Relevance
“…Heme, chlorophyll, cobalamin (vitamin B 12 ), siroheme and coenzyme F 430 belong to a family of prosthetic groups that are characterized by their tetrapyrrole-derived nature and contain a central, complexed metal ion: Fe 2+ in heme and siroheme, Mg 2+ in chlorophyll and bacterio-chlorophyll, Co 2+ in cobalamin, and Ni 2+ in coenzyme F 430 [5,6,8,9]. All of these molecules are derived from a common tetrapyrrole, uroporphyrinogen III ( Figure I), and require the function of specific enzymes or chelatases for the insertion of their metal ion ( Figure I).…”
Section: Box 1 Chelatases: Members Of a 'Functional' Family?mentioning
confidence: 99%
See 3 more Smart Citations
“…Heme, chlorophyll, cobalamin (vitamin B 12 ), siroheme and coenzyme F 430 belong to a family of prosthetic groups that are characterized by their tetrapyrrole-derived nature and contain a central, complexed metal ion: Fe 2+ in heme and siroheme, Mg 2+ in chlorophyll and bacterio-chlorophyll, Co 2+ in cobalamin, and Ni 2+ in coenzyme F 430 [5,6,8,9]. All of these molecules are derived from a common tetrapyrrole, uroporphyrinogen III ( Figure I), and require the function of specific enzymes or chelatases for the insertion of their metal ion ( Figure I).…”
Section: Box 1 Chelatases: Members Of a 'Functional' Family?mentioning
confidence: 99%
“…Subsequent studies in solution and with enzymatic systems led to the formulation of a general reaction mechanism for the metalation of porphyrins [12][13][14][15]. The steps for the mechanism include, first, deformation of the porphyrin ring; second, outer-sphere association of the solvated metal ion and the porphyrin; third, exchange of a coordinated solvent molecule with the first pyrrolenine nitrogen atom; fourth, chelate-ring closure with liberation of additional solvent molecules to form the 'sitting-atop complex'; fifth, first deprotonation of a pyrrole nitrogen atom; and last, deprotonation of the second pyrrole nitrogen with formation of the metalated porphyrin ( Figure Ib).…”
Section: Reaction Mechanism Of Porphyrin Metalationmentioning
confidence: 99%
See 2 more Smart Citations
“…S1 in Supporting Information). This demonstrated that the sitting-atop (SAT) complex [Cu(H2TEHPPS)] 2+ had been produced as an intermediate, [29][30][31] and then the protons on two of the pyrrole nitrogen atoms could be lost to form Cu-TEHPPS upon subjecting the complexes to heat (95 C) for 10 min. 32 In order to validate this mechanism, an NMR titration experiment was used.…”
Section: Absorption Property Of H2tehpps With Cu 2+mentioning
confidence: 99%